Renal Parameters in Mild, Moderate, and Chronic Cigarette Smokers - Dinesh Kumar; Preeti Sharma; Sudeep Kumar; Sumesh Prasad Sah; Manisha Arora; Shahid Iqbal; Pradeep Kumar (International Journal of Integrated Health Sciences, 2022)
Objective: To explore the link between cigarette smoking and kidney function through renal parameter assessment.